2014
DOI: 10.1016/j.ymeth.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Cow’s milk allergy: From allergens to new forms of diagnosis, therapy and prevention

Abstract: The first adverse reactions to cow’s milk were already described 2000 years ago. However, it was only 50 years ago that several groups started with the analysis of cow’s milk allergens. Meanwhile the spectrum of allergy eliciting proteins within cow’s milk is identified and several cow’s milk allergens have been characterized regarding their biochemical properties, fold and IgE binding epitopes. The diagnosis of cow’s milk allergy is diverse ranging from fast and cheap in vitro assays to elaborate in vivo assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
1
28

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 225 publications
1
169
1
28
Order By: Relevance
“…Prospective studies, performed in various countries, showed that about 2.5% of children in the first year of life have allergic reactions to cow's milk, which is therefore considered the main cause of allergies in children [12].…”
Section: Cow's Milk Protein Allergymentioning
confidence: 99%
“…Prospective studies, performed in various countries, showed that about 2.5% of children in the first year of life have allergic reactions to cow's milk, which is therefore considered the main cause of allergies in children [12].…”
Section: Cow's Milk Protein Allergymentioning
confidence: 99%
“…Atopic dermatitis is a major manifestation of this allergy (Botteman and Detzel 2015). Respiratory allergies include asthma, rhinitis, wheezing, coughing, and laryngeal edema (Hochwallner et al 2014). Gastrointestinal upsets like diarrhea, abdominal pain, nausea, vomiting are observed (Kattan et al 2011).…”
Section: Quality Improvement/combination With Other Supplementmentioning
confidence: 99%
“…The panel of pollen allergens contained allergens useful for the identification of the genuine sensitizing pollen species as well as cross-reactive allergens [53,54]. Furthermore, attempts were made to include relevant food allergens from, e.g., nuts, peanuts, milk and several other allergen sources [55][56][57][58][59]. Column "CCD" (cross-reactive carbohydrate determinants) in Table 1 indicates glycosylated allergen molecules with confirmed reactivity to CCD-specific IgE.…”
Section: Examples Of Detecting Early Allergen-specific Ige Responses mentioning
confidence: 99%